Biomechanical analysis of porous and dense dental implant-supported bridges in healthy and osteoporotic bones - Hassan Mehboob; Abdelhak Ouldyerou; Abdulsalam A. Al-Tamimi; Ali Mehboob; Imad Barsoum (PLoS ONE, 2025)
Despite the high success rate of crown bridge dental implants, peri-implant bone resorption remains a persistent major biomechanical issue. This study examines the impact of the implant’s Young’s modulus, implantation technique, and loading conditions on bone remodeling in the region of interest (ROI) for varying bone qualities. Three-dimensional finite element models of three-unit bridge crowns (TUB), implants, and cancellous and cortical bones were constructed using SolidWorks software. Four implantation scenarios, two bone health conditions (healthy and weak bone), and dense and effective porous implants were simulated under two loading conditions (200 N and gradually decreasing 100 N, 80 N, and 40 N), employing Abaqus software, for 16 cases (n = 16). A user’s subroutine was programmed using Python to estimate the iterative changes (46 simulations of each case) in bone density at peri-implant bone. The simulated results demonstrated that effective porous implants outperformed and showed higher Young’s moduli in the ROI compared to the dense implants when a single implant was implanted. However, when two implants were inserted simultaneously, the effective porous implant outperformed in the case of healthy bone only.